Retail Internationalization in China Expansion of Foreign Retailers - Siebers, L. Qixun. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2011)
As potentially the largest retail market, China has attracted a great number of foreign retail operations. Based on case study research, this book provides valuable insights international retailers need for success in China. The newly developed theoretical model helps to extend the body of knowledge on firm internationalization.